2008
DOI: 10.3181/0702-rm-49
|View full text |Cite
|
Sign up to set email alerts
|

Chemotherapy-Induced Mucositis Is Associated with Changes in Proteolytic Pathways

Abstract: Mucositis, a common toxic side effect of chemotherapy, is characterized by an arrest of cell proliferation and a loss of gut barrier function, which may cause treatment reduction or withdrawal. Gut integrity depends on nutritional and metabolic factors, including the balance between protein synthesis and proteolysis. The effects of methotrexate (MTX; a frequently used chemotherapeutic agent) on intestinal proteolysis and gut barrier function were investigated in rats. Male Sprague-Dawley rats received 2.5 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(56 citation statements)
references
References 35 publications
5
51
0
Order By: Relevance
“…In the placebo diet, whey proteins and TGFb-rich casein were replaced by TGFb-free casein and free glutamine by free alanine (Table 1). Mucositis was induced by three subcutaneous injections of 2.5 mg/kg MTX (Teva Pharma, Courbevoie, France) for 3 consecutive days (day 0, 1 and 2) as previously described [3,4]. Control rats received injections of saline (0.9%).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the placebo diet, whey proteins and TGFb-rich casein were replaced by TGFb-free casein and free glutamine by free alanine (Table 1). Mucositis was induced by three subcutaneous injections of 2.5 mg/kg MTX (Teva Pharma, Courbevoie, France) for 3 consecutive days (day 0, 1 and 2) as previously described [3,4]. Control rats received injections of saline (0.9%).…”
Section: Methodsmentioning
confidence: 99%
“…In rats, we recently reported that MTX treatment alters intestinal barrier function and protein metabolism [3] independent of the anorectic effect of MTX [4]. Indeed, MTX treatment was associated with a decrease of protein synthesis [4] and an increase of lysosomalmediated proteolysis in jejunal mucosa [3,4], which may contribute to the disruption of the gut barrier.…”
Section: Introductionmentioning
confidence: 97%
“…24 MTX has been shown to induce shortening or fusion of villi, and both atrophy and desquamation of the surface epithelium in various studies. [26][27][28] In the present study, the tissue sections of the rats showed normal intestinal structures in the salinetreated group.…”
Section: Discussionmentioning
confidence: 99%
“…Rapidly proliferative cells of the gastrointestinal system are vulnarable to the methotrexate toxicity. 24 In this context, we thought that naturally occurring dietary supplements could be used in combination with chemotherapy to ameliorate the mucosal damage and stimulate the tissue repairing of intestine. The major objectives of the current study were to assess the preventive effect of GE histopathologically on MTX-induced villus damage, epithelial atrophy, crypt loss, neutrophil accumulation in the lamina propria and goblet cell depletion in the small intestine of rats.…”
mentioning
confidence: 99%
“…the tubes were centrifuged for 5 min, to remove precipitate. The supernatant was used for phosphate estimation by Fiske-Subba Row method [27].…”
Section: Estimation Of Namentioning
confidence: 99%